Multi-Omics Landscape of DNA Methylation Regulates Browning in “Fuji” Apple - Wang, Lihua; Tang, Tiantian; Wang, Wenjun; Zhang, Jie; Wang, Zhidong; Wang, Fengzhong (Frontiers in Nutrition, 2022)
Browning seriously affects the quality of fresh-cut fruits, and its mechanism was thought to be polyphenol oxidase (PPO) in the past. A way of non-different PPO browning was found in our previous studies. However, the landscape of this browning way is still unclear in “Fuji” apples. Multi-omics (methylomics, transcriptomics, and proteomics) methods were performed to the global profiles of DNA methylation and gene and protein expression. We employed two natural bud mutation varieties of apple as materials and found a positive correlation between browning index (BI) and methylation (5mC%, MdCMT3, and MdCMT3c) and a negative correlation between BI and demethylation (MdROS1 and MdDME). DNA methylation inhibitor 5-azacytidine can delay apple browning. Further analysis showed that methylated-NCA1 and OMT1 increased significantly in apple browning. Methylated-NCA1 might inhibit NCA1 gene expression and resulted in the decline of catalase activity, thereafter significantly increased apple browning. These findings insight into a new pathway and landscape that DNA hypermethylation significantly accelerated the browning in “Fuji” apple.